2017
DOI: 10.18343/jipi.22.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Yields and Profits in Rice Farming with the Introduction of Varieties in Banten

Abstract: ABSTRAK

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 2 publications
1
5
0
2
Order By: Relevance
“…Dikatakan oleh [2], salah satu komponen inovasi teknologi yang banyak diadopsi petani adalah varietas unggul. Kemudian [3] , salah satu upaya meningkatkan produktivitas padi yaitu dengan mengintroduksikan varietas unggul baru dan teknologi budidayanya.…”
Section: Pendahuluanunclassified
“…Dikatakan oleh [2], salah satu komponen inovasi teknologi yang banyak diadopsi petani adalah varietas unggul. Kemudian [3] , salah satu upaya meningkatkan produktivitas padi yaitu dengan mengintroduksikan varietas unggul baru dan teknologi budidayanya.…”
Section: Pendahuluanunclassified
“…Goat manure is one type of manure that contains a lot of organic compounds. Purba [7] reported that the application of chemical fertilizers in rice cultivation increased rice yield by 17.1%. According to Istanti, Triasih [8], goat manure contains 2.325% total N, 4.045% P 2 O 5 , and 2.977% K 2 O.…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of using organic fertilizers, besides being able to fertilize the land, include improving environmental quality, reducing agricultural production costs, and improving crop quality [4]. Purba [7] stated that the response to Nitrogen, Phosphorus, and Potassium was strongly influenced by the use of organic matter. However, the provision of organic fertilizers and plant management has an effect on greenhouse gas emissions, especially methane gas emissions (CH 4 ) [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…To obtain optimum yields in tidal paddy fields, serious efforts have been made including the use of new superior varieties (NSVs) (Syahri and Somantri 2016; Jumakir and Endrizal 2017; Koesrini et al 2018;Purba and Giametri 2017;Sudarto et al 2018) and ameliorant applications (Ridho et al 2014;Handayani et al 2017). New superior varieties (NSVs) are important component in increasing crop production because of their high contribution (56-75%) compared to other varieties (Juanda 2016;Sianita 2016;Syahri and Somantri 2016).…”
Section: Introductionmentioning
confidence: 99%